Strategi Komunikasi Krisis dalam Menangani Kontroversi Es Teh Indonesia di Era Digital - Riyadi; Hafied Cangara; M.Iqbal Sultan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The rapid spread of information on social media poses significant challenges for businesses in managing crises, as seen in the case of Es Teh Indonesia in September 2022. This study analyzes the company’s response to a viral customer critique on the sweetness of its Chizu Red Velvet product. Employing Situational Crisis Communication Theory (SCCT) and Image Restoration Theory (IRT), the study aims to evaluate the effectiveness of the company’s crisis communication strategies. A qualitative literature review method was used to assess public reactions, media coverage, and the company’s legal response. The results indicate that Es Teh Indonesia’s legal action intensified public scrutiny, redirected focus to broader health concerns, and adversely affected its brand reputation. The study concludes that empathetic and transparent communication is critical in the digital era. It recommends real-time monitoring of public sentiment, open dialogue with customers, and the use of legal measures only as a last resort. These findings offer valuable insights for local businesses navigating crisis communication challenges in Indonesia's dynamic digital environment.